Determination of biogenic amines in semi-dry and semi-sweet Chinese rice wines from the Shaoxing region - Zhong, J.; Ye, X.; Fang, Zhongxiang; Xie, G.; Liao, N.; Shu, J.; Liu, D. (Pergamon, 2012)
The aim of this study was to investigate the levels of nine biogenic amines in two types of Chinese rice wine (semi-dry and semi-sweet) from the Shaoxing region. Thirty-nine samples from different manufacturers were analyzed by reversed-phase high-performance liquid chromatography and ultraviolet detection after pre-column derivatization with benzoyl chloride. Serotonin and tyramine were the most prevalent amines (100%) followed by histamine, cadaverine and putrescine (95.2–88.1%). Spermine, spermidine, 2-phenylethylamine and tryptamine were not detected in any sample. The most prominent biogenic amine was serotonin followed by putrescine, tyramine, cadaverine and histamine, their mean contents being 53.3, 24.3, 19.2, 9.08 and 8.83 mg/L, respectively. The total biogenic amine contents were variable, ranging from 29.3 to 260 mg/L, with 115 mg/L on average. Significantly higher (P < 0.05) serotonin and total biogenic amine levels were detected in semi-sweet rice wines. Significant and strong correlations (r ≥ 0.75, P < 0.01) were observed between some individual biogenic amine contents and between some individual and total biogenic amine concentrations. Three clusters comprising rice wines of different biogenic amines content profile were identified using a combination of hierarchical and k-means clustering.